ANALISIS PENDAPATAN DAN KELAYAKAN USAHA GULA AREN DI DESA TOMINI KECAMATAN TOMINI KABUPATEN PARIGI MOUTONG - Fikry, Fikry; Muis, Abdul; Tangkesalu, Dance (AGROTEKBIS, 2019)
This research aimed to analyze the income and the feasibility of palm sugar business at Tomini village of Parigi Moutong district. This research was conducted on June until July 2017. The population of sugar palm farmers was 30 people who all were taken as the research respondents. The respondents were interviewed using questionnaires. Data collected were analyzed for income and business feasibility. The average production cost was found to be IDR 3,109,144/month at a production rate of 284 kg/month.  At an average selling price of IDR 14,000/kg, the revenue generated was IDR 3,976.000 in average, thus the income of the respondents was IDR 866,856/month. The value of the return cost ratio (R/C) was 1.28 >1 indicating that the palm sugar business is feasible.